2017
DOI: 10.18632/oncotarget.16660
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 rs1800896 polymorphism is associated with increased head and neck cancer risk but not associated with its clinical stages

Abstract: BackgroundThe association of interleukin-10 rs1800896 polymorphism with head and neck cancer risk and its clinical stages has been investigated by many published studies, but the results remain inconsistent. Therefore, we conducted this meta-analysis for further investigation.ResultsSix case-control studies involving 1,781 head and neck cancer patients and 1,978 controls were yielded. The results indicated an association between rs1800896 polymorphism and increased head and neck risk [odds ratio (95%confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For instance, Li et al showed that rs1801320 polymorphism in the RAD51gene could signi cantly enhance the susceptibility to head and neck cancer ). Huang's study revealed that interleukin-10 genetic polymorphisms increases head and neck cancer risk (Huang, Song et al, 2017), UGT1A1 genetic polymorphisms were associated with susceptibility to HNSCC (Lacko, Roelofs et al, 2010). Besides, Li found that genetic polymorphisms in NFKB1 are associated with a decreased risk in head and neck cancers .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li et al showed that rs1801320 polymorphism in the RAD51gene could signi cantly enhance the susceptibility to head and neck cancer ). Huang's study revealed that interleukin-10 genetic polymorphisms increases head and neck cancer risk (Huang, Song et al, 2017), UGT1A1 genetic polymorphisms were associated with susceptibility to HNSCC (Lacko, Roelofs et al, 2010). Besides, Li found that genetic polymorphisms in NFKB1 are associated with a decreased risk in head and neck cancers .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the secretion of IL-10 is determined largely (74%) by heritable factors 23 . Several studies have found an association between the IL-10 -1082 G/A polymorphism and oral cancer,head and neck cancer 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the secretion of IL-10 is determined largely (74%) by heritable factors 23 . Several studies have found an association between the IL-10 -1082 G/A polymorphism and oral cancer,head and neck cancer 24 , 25 . Because meta-analysis is a suitable method to evaluate small effects in genetic association studies, we designed this study to systematically evaluate the association of the IL-10 -1082 G/A polymorphism with HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Association between rs1800896 polymorphism and head and neck cancer risk and its clinical stages in Caucasian and Asiatic evaluated by meta-analysis gave a significant association with head and neck cancer risk but not with the clinical stages [91]. Other analysis reports significant associations between the IL10 −1082A > G and IL10 −819 T > C polymorphism and increased risks of head and neck cancer similar population [92].…”
Section: Diseasementioning
confidence: 99%